AUTOIMMUNE HYPOTHYROIDISM IN PATIENT WITH NEUROFIBROMATOSIS-1 - Faraz, Ahmed; Nafees, Taha; Ahmed, Syed Arsalan; Rizvi, Shahraiz Shah (Journal of Ayub Medical College Abbottabad, 2015)
A 53 year old woman, diagnosed with Neurofibromatosis I with multiple neurfibromas over trunk, upper limb & lower limb, she had cafÃ© au lait spots on her abdomen skin. She was admitted to the tertiary care setup with the complains of cold intolerance, numbness in the limbs, high blood pressure & constipation, patient also had complain of weight gain, lab revealed high TSH, low Free thyroid hormones & positive anti thyroglobulin antibodies. Case was diagnosed with autoimmune hypothyroidism. This is the first case reported with such association of these two diseases.